2011
DOI: 10.1111/j.1467-9515.2011.00820.x
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Form as a Mechanism to Involve Staff, Public and Users in Public Services: A Study of the Governance of NHS Foundation Trusts

Abstract: In addition to introducing markets and market-like structures into public services, New Labour wished to promote the involvement of users and the public in decision-making in other ways than as individual consumers. One way was to involve the public in the governance of organizations. This could be done by removing public services from state control, and transferring them to mutual ownership; or by increasing public involvement in the governance of public bodies. NHS foundation trusts (FTs) were presented as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 22 publications
0
25
0
3
Order By: Relevance
“…In practice, research has shown that this model has delivered little in the way of local accountability. 34 The GB model adopted by CCGs is supposed to embody an ideal of accountability to members; it remains to be seen if this remains the most effective governance model as the commissioning landscape changes.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, research has shown that this model has delivered little in the way of local accountability. 34 The GB model adopted by CCGs is supposed to embody an ideal of accountability to members; it remains to be seen if this remains the most effective governance model as the commissioning landscape changes.…”
Section: Discussionmentioning
confidence: 99%
“…Governors have been lauded as potentially able to understand and represent the experiences of patients and staff (Lowe-Lauri, 2008;Ham and Hunt, 2008), as well as providing an alternative source of service knowledge and expertise (Allen et al, 2012). Furthermore, Governors have the potential to fill in key intelligence gaps not picked up by external healthcare regulators or by existing internal governance mechanisms often characterised by continuous restructuring and staff turnover.…”
Section: Meta Regulation Meets Deliberation: Situating the Governor Wmentioning
confidence: 99%
“…In addition, FT hospitals contain Governors comprised of people elected from the local community and staff representatives. They also include a Council of Governors intended to provide a forum to oversee and engage with the executive board across a range of hospital governance issues (Ocloo et al, 2014;Allen et al 2012). The Council has legal statutory duties for appointing or removal of the chair and other non-executive directors, appointment of the trust's auditor, and receipt of annual accounts and reports ( Table 1).…”
Section: Governing Nhs Foundation Hospital Trustsmentioning
confidence: 99%
“…FTs were introduced in the context of an evolving and diverse set of mechanisms for patient and public involvement reflecting very different discourses underpinning the involvement of service users and citizens across the public sector as a whole and the NHS in particular . The lack of an overarching framework, indicating how involvement mechanisms relate and interact, has created a confused and complex landscape for service users and staff to negotiate . In principle, FTs’ governing structures provide valuable opportunities for service users to be involved in senior‐level decision making.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, FTs’ governing structures provide valuable opportunities for service users to be involved in senior‐level decision making. However, evidence from the limited empirical research into CoGs, all of which focus on acute rather than mental health trusts, highlights that the scope for influence is constrained by the lack of clarity and agreement around who lay governors represent, and how they communicate with their constituencies. This, alongside confusion about or ignorance of other mechanisms for involvement, may result in uncertainty about the scope of power and influence held by CoGs.…”
Section: Introductionmentioning
confidence: 99%